Prognostic impact of proliferation for resected early stage 'pure' invasive lobular breast cancer: Cut-off analysis of Ki67 according to histology and clinical validation. (October 2017) - Carbognin, Luisa; Sperduti, Isabella; Fabi, Alessandra; Dieci, Maria Vittoria; Kadrija, Dzenete; Griguolo, Gaia; Pilotto, Sara; Guarneri, Valentina; Zampiva, Ilaria; Brunelli, Matteo; Orvieto, Enrico; Nortilli, Rolando; et al.
Abstract: Introduction: The intent of this analysis was to investigate and validate the prognostic potential of Ki67 in a multi-center series of patients affected by early stage 'pure' invasive lobular carcinoma (ILC). Methods: Clinical-pathological data of patients affected by ILC were correlated with overall survival and disease-free survival (OS/DFS); data from a parallel invasive ductal carcinoma (IDC) patients' cohort were gathered as well. The maximally selected Log-Rank statistics analysis was applied to Ki67 continuous variable to estimate the appropriate cut-off. The Subpopulation Treatment Effect Pattern Plot (STEPP) analysis was performed as well. Results: Data from overall 1097 (457/222 ILC: training/validation set; 418 IDC) patients were gathered. The identified optimal Ki67 cut-offs were 4% and 14% for DFS in ILC and IDC cohort, respectively. In ILC patients, the Ki67 cut-off was an independent OS predictor. Ten-years OS and DFS were 89.9% and 77.2% ( p = 0.007 ) and 79.4% and 69.2% ( p = 0.03 ) for patients with Ki67 ≤ 4% and >4%, respectively. In IDC patients, 10-years OS was 93.8% and 71.7%, p = 0.02, DFS was 84.0% and 52.6%, p = 0.0003, for patients with Ki67 ≤ 14% and >14%, respectively. In the validation set, the optimal Ki67 OS cut-off was 5%. The STEPP analysis showed that in the presence of low Ki67 values, IDC patients have a better DFS than ILC patients, while with the increase of values the prognosis tends to overlap. Conclusions: Despite the retrospective design of the study, the prognostic relevance of Ki67 (as well as its optimal cut-off) seems to significantly differ according to breast cancer histology. Highlights: Invasive lobular carcinoma (ILC) belongs to a distinct family of breast disease. The prognostic role of Ki67 for ILC has not fully compared to ductal carcinoma. This analysis showed that a Ki67cut-off of 4% discriminates the prognosis in ILC. A threshold of 15% is indicative of high Ki67 status in invasive ductal carcinoma. The cut-off found in ILC patients was externally validated.